The effect of lifestyle on the quality of life of an individual with fibromyalgia - case study - Nava, Viviane Lídia Zuchi (2011)
Fibromyalgia syndrome accounts for 1-2% of all rheumatic disorders, and 90% of patients with FMS are women. The general purpose of this case study was to evaluate the impact of lifestyle on the quality of life of a woman with fibromyalgia in different phases of the menstrual cycle. The sample of this descriptive quantitative and qualitative study was one 44-year-old woman. The instruments used were: profile of individual’s life style, visual analogicscale (VAS) to measure pain (1 to 10; mild, moderate, intense), the Nottingham health profile (NSP) to measure quality of life; and laboratory blood tests to measure serotonin concentrations. Results showed variations in the perception of pain, which ranged from moderate in the premenstrual phase, to intense on the first day of menstruation and mild on the seventh day. Plasma serotonin concentrations, although always within normal concentrations, were found to be reduced, particularly from the premenstrual phase to the 7th menstruation day. The woman’s life style did not meet the basic requirements for health benefits. Quality of life was variably impaired in the different phases of the menstrual cycle, particularly because of the woman’s lifestyle and of hormone fluctuation during the menstrual cycle, which contributed to the aggravation of the Fibromyalgia syndrome symptoms.